PENGEMBANGAN MODEL ROLE STRESSOR DALAM MEMPREDIKSI TURNOVER INTENTION PADA KANTOR AKUNTAN PUBLIK DI INDONESIA - Robby Tansy Hamdani; Suwandi Ng (AJAR, 2019)
This study aims to investigate the role of healthy lifestyle in reducing the impact of burnout caused by role ambiguity, role overload and work family conflict on turnover intention in public accounting firms in Indonesia. The sample used in the study is an auditor who works in a public accounting firm. Sample selection in this study using purposive sampling method based on certain criteria. The results of research using path analysis showed that burnout was able to mediate the relationship of role overload and work family conflict to turnover intention but was unable to mediate the relationship of role ambiguity to turnover intention. Psychological wellbeing is also able to mediate the relationship of burnout to turnover intention.